Pemanfaatan Agregat Sungai Lamasi Kabupaten Luwu Sebagai Campuran Lapisan Aspal Beton AC-WC - Inggrid Max Batara; Robert Mangontan; Alpius (Paulus Civil Engineering Journal, 2020)
This research is intended to test the characteristics of the Laston AC-WC mixture using river stones from Luwu Regency. The method in this research is to carry out a series of tests for the characteristics of coarse, fine, and filler aggregates then design the composition of the Laston AC-WC mixture and Marshall test to obtain mixed characteristics and Marshall immertion testing to obtain immersion index (IP) / residual strength index (IKS) / optimum asphalt mixture durability. The results showed that the characteristics of the pavement material in the form of river stones from Luwu Regency, met the specifications as a road pavement coating material. Through the Marshall test, the characteristics of the Laston AC-WC mixture were obtained with asphalt content of 5.50%, 6.00%, 6.50%, 7.00%, 7.50%. The results of the Marshall Immertion test of the laston AC-WC mixture with asphalt content The optimum 7.50% obtained an Immersion Index (IP) / Remaining Strength Index (IKS) of 95.37%, fulfilling the requirements of the General Specifications 2018 Division 6.